Simulation study of P, PI and PD controllers for DC motor position - Nur Naajihah, Ab Rahman; Nafrizuan, Mat Yahya (Penerbit UTEM, 2023)
DC motor position is a direct current that converts electrical energy to mechanical energy. It is known to have the exact angular position as well as a fast reaction. DC motor position is widely used in industry for example the conveyor system, x-y positioning table and others. However, the performance of the DC motor position can be influenced by a controller as well as the DC motor itself in providing outstanding performance. Therefore, this paper will discuss the performances of the DC motor position which applied different controllers tuned by the Ziegler-Nichols tuning method. Controllers that will be implemented are P, PI, and PD controllers. To validate the performance of the DC motor position derived from the DC motor circuit as well as the controllers, it will be compared between the DC motor which applied these different controllers and the DC motor position without any controller. These performances will be done by the simulation in MATLAB/Simulink software and evaluated in terms of the transient response aspects which are rise time, settling time and percentage overshoot. At the end of the study, it portrayed that the DC motor position with the P controller has an outstanding performance compared to the DC motor position without any controller and other controllers.